In Vitro and in Vivo Induction of Cryofibrinogen and “Paracoagulation” by Reptilase - Harder, A.J; Straub, P.W (Thrombosis and Haemostasis, 1972)
Small doses of Reptilase, a snake venom enzyme which exclusively liberates fibrinopeptide A from fibrinogen, leads to formation of cryofibrinogen as well as ethanol- and protamine-precipitability of plasma both in vitro and in vivo. Precipitates obtained in vitro were shown to contain both fibrinogen and fibrin monomer. At 20° C Reptilase-treated fibrinogen solutions contained complexes with a sedimentation rate of 11-11.6 s20W, similar to those observed after thrombin. The artificial production of cryofibrinogenemia in volunteers is discussed in relation to spontaneously occurring cryofibrinogenemias in patients with intravascular coagulation.